2018
DOI: 10.1002/cpp.2183
|View full text |Cite
|
Sign up to set email alerts
|

Treating complicated grief and posttraumatic stress in homicidally bereaved individuals: A randomized controlled trial

Abstract: Homicidally bereaved individuals may experience symptoms of Complicated Grief (CG) and Posttraumatic Stress Disorder (PTSD). This Randomized Controlled Trial examined the effectiveness of an 8-session treatment encompassing Cognitive Behavioural Therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR) to reduce self-rated CG and PTSD symptoms in 85 Dutch adult homicidally bereaved men and women. We compared changes in symptoms of CG (assessed using the Inventory of Complicated Grief) and PTSD (as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 43 publications
(58 reference statements)
1
42
1
18
Order By: Relevance
“…Eight sessions have shown to be sufficient to yield clinically relevant effects in prior research. 40 Following Dutch guidelines for grief-specific CBT, 42 central components of the treatment are exposure, cognitive restructuring and behavioural activation. In the first session, psychoeducation is offered, including information about possible emotional reactions to the death of a loved one in a traffic accident and processes that might foster or hamper recovery.…”
Section: Interventionmentioning
confidence: 99%
“…Eight sessions have shown to be sufficient to yield clinically relevant effects in prior research. 40 Following Dutch guidelines for grief-specific CBT, 42 central components of the treatment are exposure, cognitive restructuring and behavioural activation. In the first session, psychoeducation is offered, including information about possible emotional reactions to the death of a loved one in a traffic accident and processes that might foster or hamper recovery.…”
Section: Interventionmentioning
confidence: 99%
“…This self-report questionnaire includes 15 items rated on 4-point scales ranging from 0 (not at all), 1 (rarely experienced), 3 (sometimes experienced), to 5 (often experienced), the summation of which provides an index of traumatic stress. A score of 26 was used as a cut-off for clinically relevant scores (23,34). The scale has sound psychometric properties (34).…”
Section: Impact Of Event Scale (Ies)mentioning
confidence: 99%
“…Although the emotional consequences of homicidal loss evidently merit clinical attention, options for preventive and curative treatments are scarce. In existing literature on the treatment of traumatic loss, grief-and trauma-focused interventions are described, as well as interventions integrating working mechanisms of both (23,24). For the treatment of PTSD, trauma-focused cognitive behavioral therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR) are implemented in treatment guidelines (25).…”
Section: Introductionmentioning
confidence: 99%
“…Post‐treatment responses appeared to be influenced by high distress, female gender, positive relationship with the deceased, and type of relationship (e.g., loss of a child), but were not influenced by the time since loss, and type of death (homicide vs. nonhomicide). In contrast, van Denderen, de Keijser, Stewart, and Boelen () found that both eye movement desensitization and reprocessing and cognitive behaviour therapy (CBT) seem promising treatments for homicidally bereaved individuals, regardless of their gender and the passage of time since the loss. These contradictory findings prompted us to examine the relevant factors predicting the treatment outcomes targeted at specific groups (e.g., widowed older adults).…”
Section: Introductionmentioning
confidence: 99%